1987
DOI: 10.1038/icb.1987.28
|View full text |Cite
|
Sign up to set email alerts
|

The follicle‐associated epithelium of the ileal Peyer's patch in ruminants is distinguished by its shedding of 50 nm particles

Abstract: Summary. Significant differences were found between the fotlicle-associaied epilhelial cells (FAE) covering Ihe domes of the jejunal and Ileal Peyer's patches (PP) in calves. Whereas the FAE of ihe jejunal PP had scattered membraneous (M) cells among absorptive epiihetial cells, the FAE of the ileal PP constituted a homogeneous popuiaiion of cells different from both absorptive cells and M cells. The FAE of the ileal PP had short microvilli or folds, cyioplasmic vesicle,s and vacuoles containing acid phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…ln a previous study it was reported that the FAE of the ileal PP in ruminants release 50 nm membrane-bounded particles from their lateral plasma membrane (1). We now report that CA is a selective enzyme marker for the membrane-bounded particles.…”
Section: Introductionmentioning
confidence: 67%
“…ln a previous study it was reported that the FAE of the ileal PP in ruminants release 50 nm membrane-bounded particles from their lateral plasma membrane (1). We now report that CA is a selective enzyme marker for the membrane-bounded particles.…”
Section: Introductionmentioning
confidence: 67%
“…In sheep, the ileal Peyer's patch functions as an organ of post-rearrangement diversification (Reynaud et al, 1995;Weill and Reynaud, 1996) and is responsible for the vast majority of B-cell production (Reynolds and Morris, 1983;Gerber et al, 1986). The growth and function of the ileal Peyer's patch has been related to processes of epithelial differentiation (Landsverk, 1987;Landsverk et al, 1987Landsverk et al, , 1990 (Reynolds, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The surface of the dome region is covered by the follicle-associated epithelium (FAE) comprising M (microfold) cells (13), whose function is to selectively sample and transport luminal Ags, including proteins and microorganisms (14). The numbers of M cells vary between species, ranging from percentages as low as 2% of the FAE in humans (15) to an almost homogeneous population in the ruminant ileal Peyer's patch (16,17). The differentiation and uptake processes of M cells are poorly defined (18), mainly because their scarcity in the intestinal mucosa has hampered their cellular and biochemical studies.…”
Section: Peyer's Patches M Cells and Dendritic Cells (Dc) 3 In Intementioning
confidence: 99%